Africa - Making Development Climate Resilient : A World Bank Strategy for Sub-Saharan Africa - World Bank (World Bank, 2012)
This strategy for making development Climate-Resilient in Sub-Saharan Africa is the World Bank's operational response to climate variability and change on the continent. Grounded in a climate risk review of the Africa Region's sustainable development portfolio, it adds the climate change dimension to the Region's development strategy and business plan, the Africa Action Plan (AAP, 2009-2012), and will be an integral part of the AAP in the future. The AAP and the climate change strategy are a sound and realistic framework for climate-resilient development in Sub-Saharan Africa. The strategy is based on the premise that increased climate variability threatens the development gains of African countries, and that these effects need to be anticipated so that development efforts can be made more resilient to climate change. Climate has always featured prominently in African development, and people across the continent have been living with and adapting to a high degree of climate variability and its associated risks for many centuries. Yet the accelerated changes in the climate and increasing incidence of climatic disasters (floods, droughts, cyclones) during the last century, and the scientific consensus that Africa is the continent most vulnerable and least able to cope with these changes, have brought these risks into sharper focus, and made the need to address them more urgent.